Retinoic acid regulates Kit translation during spermatogonial differentiation in the mouse - Busada, Jonathan T.; Chappell, Vesna A.; Niedenberger, Bryan A.; Kaye, Evelyn P.; Keiper, Brett D.; Hogarth, Cathryn A.; Geyer, Christopher B. (Developmental biology, 2015)
In the testis, a subset of spermatogonia retains stem cell potential, while others differentiate to eventually become spermatozoa. This delicate balance must be maintained, as defects can result in testicular cancer or infertility. Currently, little is known about the gene products and signaling pathways directing these critical cell fate decisions. Retinoic acid (RA) is a requisite driver of spermatogonial differentiation and entry into meiosis, yet the mechanisms activated downstream are undefined. Here, we determined a requirement for RA in the expression of KIT, a receptor tyrosine kinase essential for spermatogonial differentiation. We found that RA signaling utilized the PI3K/AKT/mTOR signaling pathway to induce the efficient translation of mRNAs for Kit, which are present but not translated in undifferentiated spermatogonia. Our findings provide an important molecular link between a morphogen (RA) and the expression of KIT protein, which together direct the differentiation of spermatogonia throughout the male reproductive lifespan. •Retinoic acid (RA) is required for KIT activation in neonatal spermatogonia in vivo.•RA induces efficient translation of Kit mRNAs independent of STRA8 function.•RA-induced KIT activation requires signaling through the PI3K/AKT pathway.•RA increases phosphorylation of mTOR and EIF4EBP1.